Nuclear genetic diversity and structure of Anastrepha ludens wild populations evidenced by microsatellite markers - Gálvez-Reyes, Nancy; Salvador-Figueroa, Miguel; Santini, Nadia S.; Mastretta-Yanes, Alicia; Núñez-Farfán, Juan; Piñero, Daniel (Frontiers in Ecology and Evolution, 2022)
The Mexican fruit fly, Anastrepha ludens is an important pest that causes widespread damage to a number of fruit crops in Mexico. The Sterile Insect Technique (SIT) is commonly used for its control. However, the existence of natural barriers can give rise to a population structure in neutral loci and possibly behavioral or adaptive traits that interfere with SIT. For this reason, it is important to understand the genetic diversity and structure of A. ludens populations and to better understand the evolutionary ecology and population processes in view of possible expansions and possible host shifts due to climate change. We genotyped nine nuclear DNA (nDNA) microsatellite loci among fruit fly populations collected from five biogeographic areas within Mexico, Mexican Plateau, the Northeastern Coastal Plain, the Pacific Coast, the Gulf Coast of Mexico, the Soconusco and a laboratory strain. The nuclear genetic diversity was moderate (from He = 0.34 to He = 0.39) within the wild mexfly population. We found that populations were clustered in three genetic groups (K=3). The diversity and genetic structure of A. ludens are produced by environmental and geological conditions as well as local conditions like anthropogenic perturbation which would produce population expansion and the existence of possible predators that would affect the population density. Gene flow showed recent migration among populations. The laboratory strain showed less diversity than the wild samples. Large values of current and ancestral population size suggest high resistance to climatic changes, probably due to biological attributes, such as its polyphagous, multivoltine and high dispersal characteristics. In particular ecosystem fragmentation and perturbation as well as the existence of new plant hosts all of which would probably increase the abundance of flies.